A supraorbital nerve Schwannoma: a case report - Juan, Orson R.; Baas, Manuel A.; Juan, Tomiko I.; Lezama, Frida I.; Lozano, Jose L. (International Journal of Research in Medical Sciences, 2025)
Schwannomas are encapsulated tumors that originate in the peripheral this frequently affect sensory nerves, benign and with low incidence, characterized by a tumor under the skin, usually encapsulated, composed of well-differentiated neoplastic Schwann cells. They are the most common benign tumors of peripheral nerves of the head and neck region and in the extensor aspects of the limbs, but also in the spinal and cranial nerves, especially the vestibular nerve. We present the case of a female patient with schwannoma of the supraorbital nerve with neurological involvement associated with a progressively growing mass in the frontal region of the forehead. We show the clinical diagnosis process and the surgical treatment instituted to perform complete resection and functional preservation, with a definitive anatomopathological diagnosis of supraorbital schwannoma. Due to the infrequency of this pathology, we also perform a review of the literature on the subject.